Teknologisen kehityksen vaikutus työllisyyteen - Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2021)
– In order to understand the employment effects of technological progress, it is useful to separate three types of technologies: 1) automation technologies, 2) technologies that create new tasks, and 3) capital- or labor-augmenting technologies. These different types of technological advances affect employment very differently and through different channels. Automation technologies may either decrease or increase employment, whereas the other types of technological progress unambiguously increase employment. Empirical estimates of the employment effects of automation are very different in different countries. The results from United States show negative employment effects, whereas German and French studies show the opposite. It is likely that the employment effects of automation technologies depend on the role of international trade, labor market institutions and political choices. However, there is still little research on these topics. There is even less research on how the direction of technological change (automation technologies vs. technologies creating new tasks) is determined and how it can be affected by policy.
Keywords: O33; J21; J23; J24; 330; Technological change; Employment; Robots; Artificial intelligence